1998
DOI: 10.1007/s004390050736
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine β-hydroxylase: two polymorphisms in linkage disequilibrium at the structural gene DBH associate with biochemical phenotypic variation

Abstract: Levels of the enzyme dopamine beta-hydroxylase (DbetaH) in the plasma and cerebrospinal fluid (CSF) are closely related biochemical phenotypes. Both are under strong genetic control. Linkage and association studies suggest the structural gene encoding DbetaH (locus name, DBH) is a major locus influencing plasma activity of DbetaH. This study examined relationships of DBH genotype determined at two polymorphic sites (a previously described GT repeat, referred to as the DBH STR and a single-base substitution at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(120 citation statements)
references
References 37 publications
3
114
3
Order By: Relevance
“…[25][26][27][28] Current study We previously showed that a silent single nucleotide polymorphism at the 3Ј end of DBH exon 2, DBH* 444g/a, comprised of either guanidine (g) or adenine (a) at cDNA nucleotide position 444 29 associated with plasma and CSF D␤H in European-Americans (EA). 22 The a-containing allele, DBH*444a, associates with low D␤H levels, while the g-containing allele, DBH* 444g, associates with higher D␤H levels. Here, we report a second di-allelic polymorphism at DBH that associates with plasma levels of D␤H in EA.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] Current study We previously showed that a silent single nucleotide polymorphism at the 3Ј end of DBH exon 2, DBH* 444g/a, comprised of either guanidine (g) or adenine (a) at cDNA nucleotide position 444 29 associated with plasma and CSF D␤H in European-Americans (EA). 22 The a-containing allele, DBH*444a, associates with low D␤H levels, while the g-containing allele, DBH* 444g, associates with higher D␤H levels. Here, we report a second di-allelic polymorphism at DBH that associates with plasma levels of D␤H in EA.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…Strong evidence shows that: (1) plasma and cerebrospinal fluid D␤H levels are genetic traits; 17,18 (2) DBH is the major locus controlling both of these traits, [19][20][21][22] accounting for Ͼ80% of the genetic variance in plasma D␤H levels; 20 and (3) specific alleles of polymorphisms located near the 5Ј portion of the DBH gene are associated with lower D␤H levels in both plasma and CSF. 22 D␤H phenotypes and psychosis: association of low plasma and CSF D␤H levels with vulnerability to positive psychotic symptoms Previous studies support associations between low plasma or CSF levels of D␤H and elevated vulnerability to psychosis. Thus, schizophrenic patients with low CSF levels of D␤H exhibit more acute psychotic symp-…”
Section: Evidence For Genetic Influences On Vulnerability To Drug-indmentioning
confidence: 99%
“…9 The DBH gene contains 12 exons that span approximately 23 kb of human chromosome 9 ( Figure 1). A schematic representation of the DBH gene, showing the relative positions of the SNPs, is shown as Figure 1 below.…”
Section: Samplesmentioning
confidence: 99%
“…19 The primers were: 5 0 -CTGTATTTG GAACTTGGCATC-3 0 (forward) and 5 0 -AGG CATTTTACTACCCAGAGG-3 0 (reverse). Methods for genotyping the other SNPs have been published previously 7,9,11 and are available from the corresponding author (JFC).…”
Section: Samplesmentioning
confidence: 99%
“…27, NO. 4 study is known to be in significant linkage disequilibrium (Daly et al 1999) with polymorphisms (in promoter and exon 2 regions) associated with reduced DBH enzyme activity (Cubells et al 1998). In experimental animals with decreased serum DBH, reduced conversion of dopamine to noradrenaline lessens negative feedback on tyrosine hydroxylase (Anden et al 1973; Axelrod and Weinshilboum 1972).…”
Section: The Contribution Of Molecular Genetic Studies To a Dopamine mentioning
confidence: 99%